Perovskite Photoemitters: Atomically Thin Sheets of Lead‐Free 1D Hybrid Perovskites Feature Tunable White‐Light Emission from Self‐Trapped Excitons (Adv. Mater. 23/2021). Issue 23 (8th June 2021) - Klement, Philip; Dehnhardt, Natalie; Dong, Chuan‐Ding; Dobener, Florian; Bayliff, Samuel; Winkler, Julius; Hofmann, Detlev M.; Klar, Peter J.; Schumacher, Stefan; Chatterjee, Sangam; Heine, Johanna
Abstract : In article number 2100518, Johanna Heine and co‐workers report tunable white‐light emission from atomically thin sheets of the 1D hybrid perovskite [C7 H10 N]3 [BiCl5 ]Cl. The unique structure enables self‐trapped‐exciton formation with white‐light emission, and reveals the thickness dependence of the exciton self‐trapping. This enables facile control of the emission color in next‐generation lighting and display technologies.